FRIEDRICH FROEBEL’S PEDAGOGICAL CONCEPT WITHIN POLISH PRE-SCHOOL EDUCATION – THE REVIVAL OF 19TH CENTURY THOUGHT IN MODERN INSTITUTIONAL UPBRINGING OF CHILDREN - ROSZAK, MAGDALENA (Society Register, 2018)
The article presents the profile of Friedrich Wilhelm August Froebel (1782-1852), the basic postulates of his philosophy and pedagogy. It describes the origin of kindergartens, which became the bedrock of young child education spreading across the world, and the birth of the institution of kindergarten. Froebel’s thought reached many countries, among others Great Britain, USA and Poland, thanks to its popularizers. The first Polish kindergarten was set up thanks to Teresa Mleczkowa. However, it was Maria Weryho-Radziwiłowiczowa (1858-1944), who contributed the most to the popularization of Froebel’s pedagogy. Together with J. Strzemeska, she developed the methodology of working with young children on the basis of Froebel’s concept. She adjusted Froebel’s pedagogy to Polish conditions by rejecting some of its elements and adding some new ones. Unfortunately, the 20th century in Polish pedagogy was a moment, when F. Froebel was forgotten. The situation was very different in the international arena: there were institutions arising in the world, which through publications and research spread the views of the German pedagogue. Modern Polish popularizers of Froebel (among others Barbara Bilewicz-Kuźnia, Froebel.pl association) undertook to interpret the thought of F. Froebel and with a new curriculum proposal for preschool education The Gift of Play they are trying to revive Froebel’s pedagogy by adjusting it to the modern conditions. As a result of their actions, more and more kindergartens are transformed into Froebel preschools. However, they are still considered pedagogical alternatives.